Visual outcome, endocrine function and tumor control after fractionated stereotactic radiation therapy of craniopharyngiomas in adults: findings in a prospective cohort. (4th March 2017) - Astradsson, Arnar; Munck af Rosenschöld, Per; Feldt-Rasmussen, Ulla; Poulsgaard, Lars; Wiencke, Anne Katrine; Ohlhues, Lars; Engelholm, Svend Aage; Broholm, Helle; Hansen Møller, Emil; Klose, Marianne; Roed, Henrik; Juhler, Marianne
Abstract: Background: The purpose of this study was to examine visual outcome, endocrine function and tumor control in a prospective cohort of craniopharyngioma patients, treated with fractionated stereotactic radiation therapy (FSRT). Material and methods: Sixteen adult patients with craniopharyngiomas were eligible for analysis. They were treated with linear accelerator-based FSRT during 1999–2015. In all cases, diagnosis was confirmed by histological analysis. The prescription dose to the tumor was 54 Gy (median, range 48–54) in 1.8 or 2.0 Gy per fraction, and the maximum radiation dose to the optic nerves and chiasm was 54.2 Gy (median, range 48.6–60.0) for the cohort. Serial ophthalmological and endocrine evaluations and magnetic resonance imaging (MRI) scans were performed at regular intervals. Median follow-up was 3.3 years (range 1.1–14.1), 3.7 years (range 0.8–15.2), and 3.6 years (range 0.7–13.1) for visual outcome, endocrine function, and tumor control, respectively. Results: Visual acuity impairment was present in 10 patients (62.5%) and visual field defects were present in 12 patients (75%) before FSRT. One patient developed radiation-induced optic neuropathy at seven years after FSRT. Thirteen of 16 patients (81.3%) had pituitary deficiency before FSRT, and did not develop further pituitary deficiency after FSRT. Mean tumor volume pre-FSRT was 2.72 cm 3 (range 0.20–9.90) and post-FSRT 1.2 cm 3 (range 0.00–13.10). Tumor control rate was 81.3% at two, five, and 10 years after FSRT. Conclusions: FSRT was relatively safe in this prospective cohort of craniopharyngiomas, with only one case of radiation-induced optic neuropathy and no case of new endocrinopathy. Tumor control rate was acceptable.